MECHANISMS FOR IMPLEMENTING STATE POLICY OF RATIONAL USE OF HEALTH PRODUCTS - Sotnikova, Ludmila (Theory and Practice of Public Administration, 2019)
The issues of forming a holistic system of health products sale are covered and the proper approaches to it are substantiated. The mechanisms for implementing the state policy of ensuring the rational use of medicines as a component of the relevant integrated mechanism have been identified. It has been proved that the rational use of medicines is an important component of a strategy for implementation of the state policy of providing the population with health products. It was noted that one of the mechanisms for creating conditions for a rational use of medicines is introduction of a formulary system, that is, a set of management techniques in healthcare, which would ensure the application of rational, organizationally and economically effective methods of health products supply and use. Attention is drawn to the fact that implementation of an effective integrated multilevel formulary system is by far the only and an uncontested means of ensuring the effectiveness and rational use of health products on clear and comprehensible principles of functioning. It has been found that the complex mechanism for implementing the state policy of ensuring the rational use of health products consists in combining the organizational principles of application of priority technologies, forms, methods, instruments and measures (general and special) of state regulation (organizational, legal, administrative, social, economic, information, motivational), aimed at reconciling the interests of all subjects of relations in the healthcare system at different levels of providing medical care and medication supply.